Low-level laser therapy for osteonecrotic lesions: effects on osteoblasts treated with zoledronic acid - Basso, Fernanda Goncalves [UNESP]; Silveira Turrioni, Ana Paula [UNESP]; Soares, Diana Gabiela [UNESP]; Bagnato, Vanderlei Salvador; Hebling, Josimeri [UNESP]; Souza Costa, Carlos Alberto de [UNESP] (Springer, 2014)
Clinical studies have shown that low-level laser therapy (LLLT) can improve local tissue healing of bisphosphonate-induced osteonecrosis of the jaw. However, the effects of laser irradiation on bisphosphonate-treated osteoblasts have not been completely elucidated.Human osteoblasts were cultured in plain culture medium (DMEM). After 48 h, plain DMEM was replaced by DMEM with no fetal bovine serum, for a 24-h incubation followed by addition of zoledronic acid (5 mu M) for additional 48 h. Cells were subjected to LLLT (InGaAsP; 780 +/- 3 nm; 0.025 W) at 0.5, 1.5, 3, 5, and 7 J/cm(2), three times every 24 h. Cell viability, total protein production, alkaline phosphatase activity (ALP), mineral nodule formation, gene expression of collagen type I and ALP, and cell morphology were evaluated.LLLT at 0.5 J/cm(2) increased cell viability of cultured osteoblasts. ALP activity and gene expression, in addition to mineral nodule formation and Col-I gene expression, were not increased by LLLT. LLLT applied to ZA-treated cells increased Col-I expression at 0.5, 1.5, and 3 J/cm(2) but did not improve any other cell activity assessed.LLLT showed limited effects on bisphosphonate-treated osteoblasts.
Keywords: Bisphosphonates; Osteonecrosis; Osteoblasts; Low-level laser therapy; Cell culture